2004
DOI: 10.1007/s11249-004-8102-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness and Roughness Variations on the Abrasiveness of a Thin Boron Carbide Coating

Abstract: Boron carbide (B 4 C) is well known for its high hardness and favorable wear resistant properties. In dry sliding wear contact, it polishes its mating surface and provides fatigue resistance to coated parts. Employing such run-in coatings demands a thorough understanding of the parameters which directly influence the changes that occur in the coating abrasiveness during the polishing process. In this study, the effects of the overall coating thickness, overall coating roughness, substrate roughness and substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…The average coating abrasiveness was obtained using Equation 2 for the various macro-scale contact conditions, namely ball-, pin-and cone-on-disc, and is plotted versus the number of ball-on-disc cycles on a log-log scale in figure 2. In agreement with the previous findings by Harris et al [3,8,9] and Siniawski et al [4][5][6], the average abrasiveness of the coating, for all of the macro-scale contact conditions, decreased with increasing sliding distance following a power law scaling relationship. Because of the linear relationships shown in figure 2, it can be shown [8] that the instantaneous coating abrasiveness A n during the nth cycle is given by…”
Section: Coating Abrasiveness Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The average coating abrasiveness was obtained using Equation 2 for the various macro-scale contact conditions, namely ball-, pin-and cone-on-disc, and is plotted versus the number of ball-on-disc cycles on a log-log scale in figure 2. In agreement with the previous findings by Harris et al [3,8,9] and Siniawski et al [4][5][6], the average abrasiveness of the coating, for all of the macro-scale contact conditions, decreased with increasing sliding distance following a power law scaling relationship. Because of the linear relationships shown in figure 2, it can be shown [8] that the instantaneous coating abrasiveness A n during the nth cycle is given by…”
Section: Coating Abrasiveness Resultssupporting
confidence: 92%
“…It should be noted that all of the abrasiveness results were obtained using a constant load of 10 g, or approximately 0.1 N. A study by Harris et al [10] has indicated that the slope of the coating abrasiveness is independent of load after a certain number of cycles, except for very low loads. We also observed similar trends by comparing the slope of the ball-on-disc experiments performed using a 10 g load with our previous results from ball-on-disc experiments performed using a 100 g [3][4][5][6]8]. Although a slight shift in the initial coating abrasiveness was observed as the load was changed, a similar slope was observed irregardless of the applied load.…”
Section: Coating Abrasiveness Resultssupporting
confidence: 86%
See 3 more Smart Citations